Pendampingan Usaha Mikro Kecil Menengah (UMKM) terhadap Pemanfaatan Pemasaran, Desain, dan Pembukuan Digital pada Usaha Pawon Bulek Chips di Kelurahan Klandasan Ulu Balikpapan - Martinah Martinah; Nur Khafifah Rhogita; Dewi Rahayu Safitri; Amir Iskandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Field Work Practice (Innovation Development (PKL/PI)) is a course that must be taken as one of the graduation requirements in completing an undergraduate education degree by students of the Undergraduate Study Program (S1) at STIE Madani Balikpapan. Innovation Development (PI) is a form of service activities of STIE Madani students both undergraduate Accounting and undergraduate Management programs to the community. This activity is carried out for 3 months, from August to October 2024. One of the villages where the Innovation Development (PI) activity was carried out was the Klandasan Ulu village which was carried out by group 4. Innovation Development was carried out in the form of assistance to MSMEs Pawon Bulek Chips in RT 44 Klandasan Ulu Village and conducting seminars on marketing strategies. The seminar activities carried out were digital marketing with the title Building Brand Awarness Through Social Media: Latest Techniques and Trends. Aims to provide an understanding to MSME players and their surroundings about the importance of digital marketing in the current era. With this development, it is hoped that MSME players can reach wider marketing and further utilize digital applications to make products more developed among the community.